OHP-060 Paediatric Clinical Research: Current Situation and Pharmaceutical Constraints in France and Canada. (12th March 2013) - Guérin, A; Tanguay, C; Lebel, D; Prot-Labarthe, S; Bourdon, O; Bussières, JF
Abstract : Background: Paediatric clinical research represents a challenge and faces particular pharmaceutical constraints. Purpose: The main objective was to describe the current pharmaceutical situation in paediatric clinical research in France and Canada. The secondary objective was to identify factors that discourage paediatric clinical research. Materials and Methods: Cross-sectional survey of 12 pharmacy departments from France and 12 from Canada with an online 50-question survey (June–September 2012). The median [minimum-maximum] was calculated for each country and compared using the Mann-Whitney or Fisher's exact test. Respondents were asked to rank, in order of importance from 1–10 (1 being the most important), factors that discourage paediatric clinical research. Results: There was a similar number of ongoing paediatric clinical trials in France and Canada (38 [10–81] vs. 20 [4–178], p = 0.205). A lower number of pharmacists per hospital was observed in France (17 [11.5–35] vs. 45 [18.9–76.8], p = 0.009), but a similar number of pharmacists were assigned to clinical trials (1.5 [1–3] vs. 1.9 [0.2–17.4], p = 0.921). Institutional protocols represented the majority of paediatric clinical trials in France (61% [14–100] vs. 25% [0–100]). Similar services were offered, but the majority of French respondents offered help with institutional protocol development (91% vs. 50%, p = 0.063). The majority of respondents reported that the payment provided by the investigators was insufficient to cover pharmaceutical support costs and that formulations were not easily obtained from manufacturers. Respondents from both countries ranked more highly the same factors that discourage paediatric clinical research, such as absence of financial interest from the pharmaceutical industry (median rank 2 [1–6] vs. 4 [1–10]), prohibitive cost versus profit ratio (2 [1–3] vs. 3 [2–9]), small patient cohorts per hospital (2 [1–7] vs. 4.5 [1–10] and the non-availability of appropriate drug formulations (3 [1–9] vs. 5 [1–10]). Conclusions: Similar constraints were identified in France and Canada. Further studies are required to identify relevant incentives to better support pharmacists' role in paediatric clinical research. No conflict of interest.